Serum malondialdehyde (MDA) level as a potential biomarker of cancer progression for patients with bladder cancer - Lepara Zahid; Lepara Orhan; Fajkić Almir; Rebić Damir; Alić Jasmin; Spahović Hajrudin (Sciendo, 2020)
Introduction. Bladder cancer is the most common malignancy involving the urinary system. Recent research tends to emphasize the role of oxidative stress products in the carcinogenesis of bladder cancer. The level of oxidative stress can be measured by assessing the MDA levels. This study aimed to evaluate serum MDA levels in patients with bladder cancer, as well as to determine its potential role as a biomarker in the diagnosis of the disease and progression risk considerations.